The Application of Storytelling to Improve Children’s Knowledge and Skill About Tooth Brushing - Astha Devyana; N Nurlaila (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Brushing teeth is very influential in the process of child development. Dental health problems in children that arise are damage to primary teeth, dental caries in early childhood, deyaced teeth in children under 6 years of age. Tooth brushing education is important for early childhood as an effort to prevent dental health problems. Storytelling was chosen as an educational method because it is interesting and easily accepted by early childhood. To describe the application of storytelling to improve children’s knowledge and skill about tooth brushing. This study uses a descriptive method with a case study approach. The process of collecting data using interview and observation techniques. Respondents in this study consisted of 3 children aged between 4 – 5 years. The storytelling activity was carried out 2 times using illustrated fairy tale books. Children’s knowledge and skills were measures using observation sheets before and after brushing teeth storytelling. After the storytelling activity brushed teeth for 2 meetings, the results showed that the level of knowledge and skills of the respondents increased with an average value of 15.6. The application of storytelling brushing teeth has been successfully implemented and can increase the knowledge and skills of early childhood about brushing teeth.